2006
DOI: 10.1100/tsw.2006.164
|View full text |Cite
|
Sign up to set email alerts
|

Self-Related Health, Physical Activity and Complaints in Swedish High School Students

Abstract: The aim of this investigation was to study self-related health, physical activity and level of exertion, as well as body complaints in Swedish high school students. A total of 993 high school students aged 16–19 years participated in the study. A questionnaire was completed at school and included questions about self-related health, physical activity behavior, type of physical activity/sport, intensity, duration, possible injuries or complaints, and absence from physical training at school, during the last 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
49
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 25 publications
16
49
1
Order By: Relevance
“…The Finnish study also reported 24% to 28% of girls and 32% to 36% of boys to be extremely physical active, 4-5 times a week (14). This is somewhat more than in the present study and a Norwegian study by Alricsson et al (15), but similar to a Swedish study (9). This difference could indicate that some students reported physical activity when they have performed non organized activities, such as when they had probably walked or went by bike to school.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The Finnish study also reported 24% to 28% of girls and 32% to 36% of boys to be extremely physical active, 4-5 times a week (14). This is somewhat more than in the present study and a Norwegian study by Alricsson et al (15), but similar to a Swedish study (9). This difference could indicate that some students reported physical activity when they have performed non organized activities, such as when they had probably walked or went by bike to school.…”
Section: Discussionsupporting
confidence: 76%
“…The results of the questionnaire were analyzed using the Statistical Program for Social Science (SPSS) 15 to estimate a model for good health. The level of significance was set at 5 %.…”
Section: Discussionmentioning
confidence: 99%
“…Young adult university students who spend too much time sitting with a slouched posture during studying, computer use, or daily activities are a risk group. Moreover, sedentary behavior, inadequate nutrition, and stress in this group may increase the potential risk (23)(24)(25). Revealing accurate strategies for prevention and treatment might be of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior variables were presented in the following manner: smoking habit (smokers versus non-smokers), drinking habit (yes versus no). Stress was evaluated with the use of a likert scale with four possibilities for an answer (rarely stressed, sometimes stressed, almost always stressed and excessively stressed); however, in order to better adjust the data analysis, (rarely stressed added to sometimes stressed ) was classified as positive perception and (almost always stressed added to excessively stressed) as negative perception; while self-rated health was performed using the following question 11 : How do you evaluate your health? with five choices for an answer (very good, good, average, bad and very bad).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, some demographic and socio-economic factors as well as other related to lifestyle are directly associated with health self-evaluation in industrialists 4,5 , adults 6,7 and in the elderly 8 , being able to determine a positive or negative perception, which contributes to the development of future interventions in many population subgroups 9 . Moreover, negative self-rated health is associated with higher frequency of chronic diseases 10 , smoking over 20 cigarettes a day, insufficient levels of physical activities 11,12 , low weight or obesity 13 , female sex, advanced age, low educational background and compromised health 14 . Some studies have shown that physically active men present better self-rated health compared to the insufficiently active ones [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%